Inadvertent Port: Catheter Placement in Azygos Vein - Harish, K.; Madhu, Y. C. (International Journal of Angiology, 2012)
Totally implantable ports are safe and effective means of venous access for administration of chemotherapy. One of the usual vessels accessed, through which the port is placed, is the subclavian. Herein, we report a case where the central access was obtained through the left subclavian vein. But the catheter when it was placed was found to be in the azygos vein. This was confirmed with dye study. This is the first report of such an occurrence with subclavian access. The catheter was later withdrawn and repositioned in the superior vena cava. We recommend that the entire procedure of catheter placement must be done under fluoroscopy guidance to ensure safe and error-free positioning.
Keywords: catheter; port; azygos vein; subclavian vein